Input features for deep learning-based polyphonic sound event localization and detection - Nguyen, Thi Ngoc Tho (Nanyang Technological University, 2023)
Sound event localization and detection (SELD) is an emerging research topic that combines the tasks of sound event detection (SED) and direction-of-arrival estimation (DOAE). The SELD task aims to jointly recognize the sound classes and estimate the directions of arrival (DOAs) and the temporal activities of detected sound events. SELD has many acoustic sensing and monitoring applications, such as urban sound sensing, surveillance, wildlife monitoring, and context-aware devices such as hearing aids, smartphones, autonomous vehicles, and robots.